PKM Increasing Creativity and Economy in the Production of Digital Storytelling Videos on Social Media Platforms at the Kindergarten Teacher Activity Center (PKG) Biringkanaya District, Makassar - Hardiyanti, Sartika Dwi; Ardiansa, Ardiansa; Andu, Christine Purnamasari (Pusat Studi Pembangunan dan Pemberdayaan, 2024)
PKM to improve the creativity of teachers of the Cluster Activity Center (PKG) of Biringkanaya District, Makassar City will be an alternative for teachers in fulfilling the improvement of professionalism as educators in providing creative and innovative learning with the method of using social media. The technological tools applied in this PKM are the website which is the domain of PKG Kec. Biringkanaya and the YouTube link of PKG Kec. Biringkanaya. The website and YouTube of PKG Kec. Biringkanaya will help the cluster activity center in developing its activities in education management, increasing teacher creativity, and making this social media a place for self-development as well as income for PKG Kec. Biringkanaya in producing visual works on social media. This PKM is carried out in five stages of implementation, namely the first socialization, training to improve teacher creativity in making digital videos using the Canva and Capcut applications, training in using the PKG Kec. Biringkanaya website, mentoring stage, stage of implementing appropriate technology, and evaluation and sustainability stage. With this PKM activity, PKG Kec. partners. Biringkanaya has enthusiasm and commitment in increasing creativity and seeking income from the visual works of partners that are applied in social media, websites, and YouTube partners. This activity is the result of community service funded by the Directorate General of Higher Education, Ministry of Education and Culture of the Republic of Indonesia as the recipient of the Second Phase of Community Service Program Funding for the 2024 Fiscal Year.